Perceptions of Maternal Discrimination and Pregnancy/Postpartum Experiences Among Veterinary Mothers - Wayne, Annie S.; Mueller, Megan K.; Rosenbaum, Marieke (Frontiers in Veterinary Science, 2020)
Objective: To describe perceptions of maternal discrimination and to begin to understand patterns around timing of starting families, infertility, and post-partum depression among veterinary mothers. Design: Cross-sectional questionnaire with closed and open-ended questions posted to a social media platform “Moms with a DVM.” Sample: 1,082 veterinary mothers in the United States. Procedures: An online questionnaire was administered regarding perceived discrimination, inequities in the work-place due to pregnant or maternal status, desired accommodations, timing of pregnancy(ies), fertility issues, and postpartum experiences. Results: At least one form of perceived discrimination was reported by 819 (75.7%) respondents (M = 2.6, SD = 2.1, range 0–10). Specifically, 789 (72.9%) reported maternal discrimination. Over half of the sample (n = 632, 58.4%) reported at least one instance of perceived inequity in the workplace due to status as a mother (M = 1.23, SD = 1.4, range 0–5). A majority (906, 83.7%) reported that their career had “definitely” or “maybe” affected the timing of their children. One hundred eighty-nine respondents (17.5%) experienced at least one miscarriage, and 192 (17.6%) used fertility treatment due to difficulty conceiving. Postpartum depression was diagnosed in 181 respondents (16.7%), and 353 (32.6%) reported symptoms consistent with postpartum depression but did not seek medical care. Of 953 participants who needed accommodations for breastfeeding and/or pumping while at work, 130 (13.6%) reported excellent accommodations, 454 (47.6%) adequate, 258 (27.1%) inadequate, and 111 (11.6%) had no accommodations provided. Conclusions and Clinical Relevance: Participants reported experiences of perceived maternal discrimination, as well as inequities and lack of support services due to status as a mother. These results highlight the need for attention and changes to ensure veterinarians have supportive and sustainable career options.